Rancang Bangun Pengisian Tegangan Baterai Handphone (HP) Metoda Buck Konverter DC-DC Tipe FC75 - Parlindungan Pandapotan Marpaung (Yayasan Literasi Sains Indonesia, 2024)
Mobile phone (HP) battery manufacturing specifications have a charging current capacity maximum parameter CAh(maks.) = 800 mAh and maximum voltage Vbat(max.) = 3.7 volts dc reduces to 2.02 volts dc requires recharging. In this research HP battery voltage was recharged using the FC75 dc-dc buck converter method, starting from a voltage of Vbat(initial) = 2.02 volts until the final battery voltage was charged at Vbat(final) = 3.713 volts. The HP battery charge voltage parameter Vch comes from the output voltage of the FC75 dc-dc buck converter the parameter Vo(conv.) is expressed as Vo(conv.) = Vch. The purpose of using the FC75 dc-dc buck converter is to electronically convert the lower Vo(conv.) charger voltage (buck) to the larger Vi(conv.) input voltage to control the HP battery charger output power equal to the input power. The results of the research on controlling the output power of the HP battery charger of Po(conv.) = Pi(conv.) = 0.579 watts, there was an increase in the final charger voltage Vokonv.(final) along with the increase in the final HP battery voltage Vbat(final) being charged. The increase in the final charger voltage reaches Vokonv.(final) = Vbat(final) = 3.713 volts, the final charger current becomes Ich(final) = 0.156 A and remains towards the HP battery during charging with a difference in the decrease in charger current towards the HP battery of ∆Ich = 0.009 A relatively small is still profitable, because it avoids back current to the charger voltage.